Disordered metasurface-enhanced perovskite composite films with ultra-stable and wide color gamut used for backlit displays. (September 2022) - Wu, Zhihai; Zhang, Yichen; Du, Bintao; Yang, Keyang; Wu, Jun; Dai, Tianyi; Dong, Chengkun; Xia, Jun; Wu, Anlang; Zhao, Zhenfu
Abstract: Perovskite nanocrystals (PNCs) are promising to replace the traditional phosphor color conversion layers in backlit displays due to their excellent optical properties, which can enhance the color gamut and saturation of displays. However, poor stability and low luminescence efficiency hinder the development of perovskite-based devices. Here, inspired by the Yunnan cicada wing, a low-cost, easy-to-fabricate, and large-area (> 78 cm 2 ) all-dielectric metasurface based on the Purcell effect is developed to tune and improve the light extraction efficiency of PNCs. All-dielectric metasurfaces composed of weakly disordered TiO2 /PS spheres are embedded in the PNCs/PVDF ( Poly (vinylidene fluoride)) films prepared by in-situ fabrication strategy, resulting in 3.19-fold photoluminescence (PL) maximum enhancement of these composite films. The stability of PNCs is also markedly improved after PVDF encapsulation. As an application demo, these all-dielectric metasurface-modulated perovskite composite films are applied in LCD backlit, with the color gamut of 157% of commercial LCD and 107% of NTSC, showing tremendous potential in high-end lighting and display. Furthermore, combined with the scalability of large-area fabrication, cost-effective weakly disordered metasurfaces are a potential method to bridge the gap between high-efficient laboratory demonstrations and commercialization in the field of display. Graphical Abstract: ga1 Highlights: A low-cost, easy-to-fabricate, and large-area metasurface is proposed and realized. The degree of disorder in position greatly affects the magnitude of resonant modes. Metasurface enhances the PL intensity of PNCs based on the Purcell effect. PVDF packaging markedly improves the photostability and humidity stability of PNCs. LCD device is designed by adopting metasurfaces modulated CsPbX3 composite films.